2017
DOI: 10.1002/bio.3294
|View full text |Cite
|
Sign up to set email alerts
|

Determination of fluvoxamine maleate in human urine and human serum using alkaline KMnO4–rhodamine B chemiluminescence

Abstract: The flow-injection chemiluminescence (FI-CL) behavior of a gold nanocluster (Au NC)-enhanced rhodamine B-KMnO system was studied under alkaline conditions for the first time. In the present study, the as-prepared bovine serum albumin-stabilized Au NCs showed excellent stability and reproducibility. The addition of trace levels of fluvoxamine maleate (Flu) led to an obvious decline in CL intensity in the rhodamine B-KMnO -Au NCs system, which could be used for quantitative detection of Flu. Under optimized cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Application of this reagent in a basic medium can overcome these problems, but very weak CL emissions are obtained when using basic KMnO 4 . Nanomaterials (especially Au nanostructures) have been applied to enhance this emitted CL . In this study, it was observed that the weak CL emission from the RhoB−KMnO 4 reaction could be effectively enhanced in the presence of Au NCs.…”
Section: Resultsmentioning
confidence: 89%
“…Application of this reagent in a basic medium can overcome these problems, but very weak CL emissions are obtained when using basic KMnO 4 . Nanomaterials (especially Au nanostructures) have been applied to enhance this emitted CL . In this study, it was observed that the weak CL emission from the RhoB−KMnO 4 reaction could be effectively enhanced in the presence of Au NCs.…”
Section: Resultsmentioning
confidence: 89%
“…Oral fluid microsampling also gave satisfying results in the monitoring of sertraline, fluoxetine, citalopram, and vortioxetine [153]. Urine can be used as a matrix for monitoring escitalopram, citalopram, fluoxetine, paroxetine, and bupropion, and it has also been proposed for the monitorization of fluvoxamine and moclobemide [154][155][156][157][158][159][160][161]. For TCAs, urine sampling can be used, even though mostly for forensic studies rather than for routinary monitoring [162].…”
Section: Tdm and Antidepressant Medicationsmentioning
confidence: 99%
“…72 A CRET system usually consists of chemiluminescence (CL) donors ( e.g. , peroxyoxalate, 73,74 lucigenin, 75–77 luminol, 78–80 KMnO 4 , 81 etc .) and suitable acceptors ( e.g.…”
Section: Chemical Energy Conversion and Applicationsmentioning
confidence: 99%